The influence of agrometeorological conditions of the vegetation period on the technological properties of grapes - Ткаченко, Оксана Борисовна; Тринкаль, Ольга Валентиновна; Пашковский, Александр Игоревич (Technology audit and production reserves, 2015)
The article discusses the impact of agrometeorological conditions of the vegetation period on the technological properties of grapes of new domestic breeding in the Odessa region in the last 3 years. The object of the study was made by the grape of varieties generative selection - Sparkle, Muscat Odessa, Flavored, Zagreus, clonal selection - Iskorka, Muskat Odesskii, Aromatnii, Zagrey, clone selection – Irsai Oliver, Feteasca Belaya, Telti Kuruk, Sukholimanskii Belyi, Rkatsiteli of harvest of 2012-2014 years. Experimental varieties are the result of breeding department of the NSC "Tairov Wine Making and Wine Growing Institute". These promising varieties and forms of new generation which have high adaptive properties to environmental factors are seen as a potential for the production of a modern white table wines. The main climatic factors (air temperature, rainfall, amount of active temperatures) during the growing season, their impact on the dynamics of complex carbohydrate-acid grape of harvest of 2012-2014 years are investigated. Dependence of optimum conditions of white grapes from the date of harvest is formulated, are recommendations for high-quality raw materials for the production of dry white wines from the preferred organoleptic properties are given.